Efficient wave-absorbing composite coating applied to microwave deicing of wind power blade
By using composite coatings filled with carbon nanotubes and silicon carbide on wind power blades, problems such as low thermal efficiency and insufficient wear resistance in wind power blade deicing technology are solved, and the effects of efficient deicing, wear resistance, corrosion and lightning protection are achieved, extending the service life of the paint.
Patent Information
- Application Number
- CN202411757891.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-07
AI Technical Summary
The prior art has problems such as low thermal efficiency, high energy consumption, difficult installation and maintenance, high cost, and susceptible to lightning damage in wind power blade deicing. The hydrophobic coating can only slow down icing and cannot completely suppress it, and the wear resistance and service life are insufficient.
Using composite coatings with synergistic filling of carbon nanotubes and silicon carbide, carbon nanotubes provide excellent wave-absorbing and heating performance. Silicon carbide improves the wear and thermal conductivity of the coating, forming a coating that is efficient wave-absorbing and heating, wear-resistant, corrosion-resistant and lightning-proof.
It realizes efficient deicing on the surface of wind power blades, improves the wear resistance, corrosion resistance and lightning resistance of the paint, extends the service life of the paint, and improves the deicing efficiency and thermal efficiency.
Smart Images

Figure CN119570302A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of microwave heating and relates to a high-efficiency microwave-absorbing composite coating used for microwave deicing of wind turbine blades. Background Art
[0002] Wind energy is a clean and renewable energy with large reserves and wide distribution. Wind power generation technology has developed rapidly, and wind power has become an important type of power source in my country. The wind resources in Central China are relatively abundant, but affected by factors such as latitude and altitude, in the low temperature environment in winter, when there is sleet or freezing rain, the surface of the wind turbine blades will freeze. In the low temperature environment in winter, when there is sleet or freezing rain, the surface of the wind turbine blades will freeze. Blade icing will affect the power generation output of the unit, causing serious economic losses and safety risks.
[0003] At present, there are several methods for deicing wind turbine blades at home and abroad: (1) Gas-heat deicing: hot air is circulated in the inner cavity of the blade, and the heat is transferred to the outer surface through the blade shell, causing the ice to melt and fall off. However, the blade weight increases significantly, the overall thermal efficiency is low, and the energy consumption is high; (2) Electric heating film deicing: electric heating film is laid on the parts of the blade surface that are prone to ice formation. After power is turned on, the blade surface is directly heated to melt the ice and fall off. However, the installation and maintenance of electric heating film are difficult, the cost is high, and it is easily damaged by lightning strikes; (3) Electromagnetic pulse deicing: a pulse coil is installed under the metal skin, and pulse discharge technology is used to generate transient electromagnetic force on the metal skin, so that the ice layer at the joint Deformation and cracking or falling off are mechanical deicing, with a small effective area, making it difficult to completely remove the ice layer, and leaving more residues; (4) Super hydrophobic coating anti-icing: using the super hydrophobic properties of the coating surface to reduce the adhesion of water droplets and delay ice formation, but super hydrophobic coatings have poor wear resistance and short life, and the nanostructure is not dust-resistant and ineffective against high-speed jet water; (5) Microwave heating deicing: a new anti-icing technology that combines microwave heating and absorbing coatings. A microwave source is installed in the inner cavity of the blade to emit microwaves, and the absorbing coating coated on the surface of the blade absorbs the microwaves to generate heat that is transferred to the water or ice on the blade, thereby playing an anti-icing role. Microwave heating acts on the inside and outside of the object at the same time, without the need for heat conduction, and has the advantages of fast heating, uniform heating, energy-saving and high efficiency, easy control, and simple maintenance.
[0004] In response to the icing problem of wind turbine blades, the existing technology has mainly done a lot of research on the anti-icing of hydrophobic coatings. Ning Yonghui developed a water-based anti-icing coating in the article "Preparation and performance influencing factors of water-based anti-icing coatings for wind turbine blades", which improved the anti-icing performance by the hydrophobicity of the coating surface; Peng Chaoyi prepared a superhydrophobic polyvinylidene fluoride coating in Preparation and anti-icing of superhydrophobic PVDF coating on a wind turbine blade, with a water contact angle of about 156° and good anti-icing performance. However, the hydrophobic coating can only slow down but not completely suppress icing. After the coating surface has undergone multiple "icing-shedding" cycles and the effects of factors such as sand and dust wear, the microstructure of the coating surface will be destroyed, resulting in a reduction in the hydrophobic and anti-icing performance of the coating. According to the operating characteristics of wind turbine blades, microwave deicing coatings for blades need to have the following properties: (1) The thickness of the blade coating should not be too large, requiring the coating's wave-absorbing filler to be small in size and high in wave-absorbing efficiency; (2) When the wind turbine is running, the blade tip speed is 50 to 70 m / s, requiring the coating to withstand long-term erosion by environmental factors such as ultraviolet rays, wind and sand, rain erosion, humidity and heat, vibration and temperature difference; (3) Control the surface resistance of the coating to avoid lightning strikes. The present invention proposes a method of using carbon nanotubes and silicon carbide to synergistically improve the long-term wave-absorbing and heating performance of blade coatings. Carbon nanotubes have excellent wave-absorbing properties, and silicon carbide has wave-absorbing properties while taking into account good wear resistance. The present invention uses carbon nanotube-filled primers and silicon carbide-filled topcoats to synergistically enhance the coating's wave-absorbing and heating, wear resistance, corrosion resistance, and lightning protection properties, thereby achieving efficient deicing of the surface of wind turbine blades and enhancing the service life of the coating. Summary of the invention
[0005] The main purpose of the present invention is to provide a high-efficiency microwave-absorbing composite coating for microwave deicing of wind turbine blades. The coating on the surface of the blade has high-efficiency microwave-absorbing performance while taking into account the multifunctionality of wear resistance, impact resistance, aging resistance, lightning protection, corrosion resistance, etc. It does not affect the aerodynamic performance of the blade, and can protect it from erosion and abrasion in severe weather such as wind, snow, and rain.
[0006] The technical solution of the present invention:
[0007] A high-efficiency microwave-absorbing composite coating used for microwave deicing of wind turbine blades comprises a composite coating composed of a primer filled with carbon nanotubes and a topcoat filled with silicon carbide.
[0008] The primer filled with carbon nanotubes is arranged on the surface of the blade, and the topcoat filled with silicon carbide is arranged on the surface of the primer filled with carbon nanotubes.
[0009] Furthermore, in the above scheme, the primer is a solvent-free polyurethane primer coating, which is composed of a curing agent and a main agent in a mass ratio of 1:1.5 to 2.5, the curing agent is an epoxy resin, and the main agent is one of toluene diisocyanate prepolymers and diphenylmethane diisocyanate prepolymers.
[0010] Furthermore, in the above scheme, the topcoat is a water-based polyurethane topcoat coating, which is composed of a curing agent and a main agent in a mass ratio of 1:5 to 7, the curing agent is a hydroxy acrylic resin, and the main agent is a hexamethylene diisocyanate prepolymer.
[0011] Furthermore, in the above scheme, the contents of the components in the primer filled with carbon nanotubes are 2-6 wt.% of carbon nanotubes, 5-10 wt.% of diluent, and 84-93 wt.% of solvent-free polyurethane primer coating.
[0012] Furthermore, in the above scheme, the contents of the components of the silicon carbide-filled topcoat are 5-10 wt.% of silicon carbide, 5-10 wt.% of diluent, and 80-90 wt.% of polyurethane topcoat.
[0013] Furthermore, in the above solution, the carbon nanotubes are multi-walled carbon nanotubes with an inner diameter of 3 to 5 nm, an outer diameter of 8 to 15 nm, and a length of 3 to 12 μm.
[0014] Furthermore, in the above solution, the particle size of the silicon carbide is 1000-1500 mesh.
[0015] Furthermore, in the above scheme, the primer diluent is a lipid solvent such as ethyl acetate and butyl acetate, and the topcoat diluent is deionized water.
[0016] Furthermore, in the above solution, the thickness of the primer is 200 to 600 μm, and the thickness of the topcoat is 50 to 200 μm.
[0017] Beneficial effects of this technical invention:
[0018] 1. Excellent microwave absorption and heating performance: The present invention adopts a composite coating filled with carbon nanotubes and silicon carbide, and utilizes the excellent microwave absorption and heating performance of carbon nanotubes and the microwave absorption and heating and thermal conductivity of silicon carbide to make the surface heating rate of the coating fast under the action of microwave radiation.
[0019] 2. Good wear resistance and impact resistance: The Mohs hardness of silicon carbide is 9.5, second only to the hardest diamond in the world (10). Due to the introduction of silicon carbide in the topcoat and the formation of a three-dimensional network in the coating matrix, the wear resistance and impact resistance of the composite coating are improved.
[0020] 3. Good anti-corrosion performance: The filling of carbon nanotubes and silicon carbide can significantly improve the density of the coating, prevent the penetration of water molecules, delay the failure of the coating, and increase the service life of the coating.
[0021] 4. Good lightning protection performance: As soon as possible, carbon nanotubes have strong electrical conductivity, but silicon carbide has weak electrical conductivity. Covering the surface of the primer filled with carbon nanotubes with a layer of topcoat filled with silicon carbide can greatly enhance the surface resistivity of the composite coating and reduce the risk of lightning strikes on the blades. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a structural cross-sectional view of the present invention.
[0023] Figure 2 This is a Bode film value diagram of the composite blade coating samples (Examples 1-2 and Application Examples 1-2) after being immersed in a simulated seawater solution for 2 months.
[0024] In the figure: 1 blade; 2 primer filled with carbon nanotubes; 3 topcoat filled with silicon carbide. DETAILED DESCRIPTION
[0025] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings and technical solutions.
[0026] like Figure 1 As shown, the outer side of the blade body 1 is provided with a filling primer 2, the outer side of the filling primer 2 is provided with a filling topcoat 3, the filling primer 2 contains carbon nanotube absorbing material, and the filling topcoat 3 contains silicon carbide wear-resistant and absorbing filler, finally forming a composite absorbing coating.
[0027] Example 1
[0028] A high-efficiency composite coating for microwave deicing of wind turbine blades
[0029] (1) Blade polishing: A real blade was selected as the coating substrate for the test. The size of the blade was 10×10×3.5 cm. The blade surface was polished and then used.
[0030] (2) Preparation of primer filled with carbon nanotubes: Take 57wt.% of polyurethane primer, 4wt.% of carbon nanotubes, and 10wt.% of ethyl acetate, add carbon nanotubes and ethyl acetate into the polyurethane primer, stir mechanically or by ball milling until the mixture is uniform, and stir at a speed of 500r / min. Then add 29wt.% of epoxy resin, stir mechanically for 5min, and stir at a speed of 200r / min. Apply by brush or spray on the blades. After each coating, place at room temperature for 24h to completely cure, and repeat the next coating to achieve the desired thickness.
[0031] (3) Preparation of silicon carbide filled topcoat: Take 70wt.% of polyurethane topcoat, 8wt.% of silicon carbide, and 10wt.% of deionized water, add silicon carbide and deionized water to the polyurethane topcoat, stir mechanically or by ball milling until the mixture is uniform, and stir at a speed of 500r / min, then add 12wt.% of hydroxyl acrylic resin, stir mechanically for 5min, and stir at a speed of 200r / min, and apply by brush or spray on the primer filled with carbon nanotubes. After each coating, place it at room temperature for 24h to completely cure, and then repeat the next coating to obtain a composite coating (filled primer 400μm, filled topcoat 200μm).
[0032] Example 2
[0033] A high-efficiency composite coating for microwave deicing of wind turbine blades
[0034] (1) Blade polishing: A real blade was selected as the coating substrate for the test. The size of the blade was 10×10×3.5 cm. The blade surface was polished and then used.
[0035] (2) Preparation of primer filled with carbon nanotubes: Take 56wt.% of polyurethane primer, 6wt.% of carbon nanotubes, and 10wt.% of butyl acetate, add carbon nanotubes and butyl acetate into the polyurethane primer, stir mechanically or by ball milling until the mixture is uniform, and stir at a speed of 500r / min. Then add 28wt.% of epoxy resin, stir mechanically for 5min, and stir at a speed of 200r / min. Apply by brush or spray on the blade. After each coating, leave it at room temperature for 24h to completely cure, and repeat the next coating to achieve the desired thickness.
[0036] (3) Preparation of silicon carbide filled topcoat: Take 73wt.% of polyurethane topcoat, 5wt.% of silicon carbide, and 10wt.% of deionized water, add silicon carbide and deionized water to the polyurethane topcoat, stir mechanically or by ball milling until the mixture is uniform, and stir at a speed of 500r / min, then add 12wt.% of hydroxyl acrylic resin, stir mechanically for 5min, and stir at a speed of 200r / min, and apply by brush or spray on the primer filled with carbon nanotubes. After each coating, place it at room temperature for 24h to completely cure, and then repeat the next coating to obtain a composite coating (300μm filled primer, 100μm filled topcoat).
[0037] Comparative Example 1
[0038] Wind turbine blade coating
[0039] (1) Blade polishing: A real blade was selected as the coating substrate for the test. The size of the blade was 10×10×3.5 cm. The blade surface was polished and then used.
[0040] (2) Preparation of primer: Take 60wt.% of polyurethane primer and 10wt.% of ethyl acetate, add ethyl acetate to the polyurethane primer, stir mechanically or by ball milling until the mixture is uniform, stirring at a speed of 500r / min, then add 30wt.% of epoxy resin, stir mechanically for 5min, stir at a speed of 200r / min, and apply by brush or spray on the blade. After each coating, leave it at room temperature for 24h to completely cure, and repeat the next coating to achieve the desired thickness.
[0041] (3) Preparation of topcoat: Take 77wt.% of polyurethane topcoat and 10wt.% of deionized water, add deionized water to the polyurethane topcoat, stir mechanically or by ball milling until the mixture is uniformly mixed, and stir at a speed of 500r / min. Then add 13wt.% of hydroxy acrylic resin, stir mechanically for 5min, and stir at a speed of 200r / min. Apply by brush or spray on the primer. After each coating, leave it at room temperature for 24h to completely cure, and repeat the next coating to obtain a composite coating (filling primer 400μm, filling topcoat 200μm).
[0042] Comparative Example 2
[0043] Wind turbine blade coating
[0044] (1) Blade polishing: A real blade was selected as the coating substrate for the test. The size of the blade was 10×10×3.5 cm. The blade surface was polished and then used.
[0045] (2) Preparation of primer: Take 60wt.% of polyurethane primer and 10wt.% of ethyl acetate, add ethyl acetate to the polyurethane primer, stir mechanically or by ball milling until the mixture is uniform, stirring at a speed of 500r / min, then add 30wt.% of epoxy resin, stir mechanically for 5min, stir at a speed of 200r / min, and apply by brush or spray on the blade. After each coating, leave it at room temperature for 24h to completely cure, and repeat the next coating to achieve the desired thickness.
[0046] (3) Preparation of topcoat: Take 77wt.% of polyurethane topcoat and 10wt.% of deionized water, add deionized water to the polyurethane topcoat, stir mechanically or by ball milling until the mixture is uniformly mixed, and stir at a speed of 500r / min. Then add 13wt.% of hydroxy acrylic resin, stir mechanically for 5min, and stir at a speed of 200r / min. Apply by brush or spray on the primer. After each coating, leave it at room temperature for 24h to completely cure, and repeat the next coating to obtain a composite coating (filling primer 300μm, filling topcoat 100μm).
[0047] Performance Testing
[0048] To demonstrate the effects of the present invention, the coating samples prepared in the above embodiments and comparative examples were subjected to the following performance tests:
[0049] 1. Wave absorption and heating performance test: Use WR430 standard rectangular waveguide antenna, microwave frequency 2.45GHz, microwave transmission power 2.5KW, irradiation distance 1m, conduct microwave surface irradiation test, and measure the temperature of the blade coating surface before and after the microwave.
[0050] 2. Wear resistance and impact resistance test: refer to GB / T23988-2009 "Determination of wear resistance of coatings - falling sand method" for testing.
[0051] 3. Anticorrosion performance test: A 20×50×2 mm iron sheet was polished, degreased, cleaned and dried, and the coatings configured in the embodiment and the comparative example were respectively applied on the treated iron sheet. After the coatings were completely cured, they were immersed in simulated seawater. After immersion for 2 months, the anticorrosion performance of the coatings was measured using the AC impedance method.
[0052] Table 1 Test results of different coatings
[0053]
[0054] As shown in Table 1, compared with the comparative example, the surface temperature of the coating in the embodiment increases significantly under the action of microwaves. After 5 minutes of 2.5KW microwave irradiation, the surface temperature of the coating in Examples 1 to 2 rises by more than 30°C, and the temperature rise rate is more than 6°C / min, which indicates that the addition of absorbing fillers can quickly increase the surface temperature of the coating to melt the ice layer on the blade surface, thereby improving the power generation capacity of the blade.
[0055] like Figure 2 As shown, after immersing in simulated seawater for 2 months, the low-frequency modulus values of Examples 1 and 2 are all greater than 10 10 Ω·cm 2 , the surface shows excellent anti-corrosion performance, while the low-frequency modulus values of comparative examples 1 to 2 are relatively low, and their low-frequency modulus values are between 10 8 Ω·cm 2 This shows that adding absorbing fillers can reduce the microscopic defects in the coating, improve the anti-penetration performance of the coating, and extend the service life of the coating.
[0056] Compared with the comparative example, the wear resistance of the embodiment is improved by 137% and 149% respectively. The introduction of silicon carbide on the coating surface enhances the wear resistance of the coating. At the same time, the surface resistance of the coating can be further reduced. The composite radar-absorbing coating reduces the risk of lightning strikes while deicing.
[0057] In summary, the composite coating prepared by the present invention has excellent heating performance under the action of microwaves, and enhances the deicing efficiency of the blade surface. At the same time, the wear resistance and anti-corrosion performance of the blade coating are improved. The excellent performance makes the present invention have strong use value.
[0058] The above is only a preferred embodiment of the present invention. For ordinary technicians in the field, several equivalent substitutions, modifications or improvements can be made without departing from the principle of the present invention. These substitutions and improvements should also be regarded as the scope of protection of the present invention.
Claims
1. A high-efficiency microwave-absorbing composite coating for microwave deicing of wind turbine blades, characterized in that: The high-efficiency microwave-absorbing composite coating used for microwave deicing of wind turbine blades comprises a composite coating composed of a primer filled with carbon nanotubes and a topcoat filled with silicon carbide.
2. The high-efficiency microwave-absorbing composite coating for microwave deicing of wind turbine blades according to claim 1 is characterized in that: The primer filled with carbon nanotubes is arranged on the surface of the blade, and the topcoat filled with silicon carbide is arranged on the surface of the primer filled with carbon nanotubes.
3. The high-efficiency microwave-absorbing composite coating for microwave deicing of wind turbine blades according to claim 1 is characterized in that: The primer is a solvent-free polyurethane primer coating, which is composed of a curing agent and a main agent in a mass ratio of 1:1.5-2.5, the curing agent is an epoxy resin, and the main agent is one of toluene diisocyanate prepolymers and diphenylmethane diisocyanate prepolymers.
4. The high-efficiency microwave-absorbing composite coating for microwave deicing of wind turbine blades according to claim 1 is characterized in that: The topcoat is a water-based polyurethane topcoat coating, which is composed of a curing agent and a main agent in a mass ratio of 1:5-7, the curing agent is a hydroxy acrylic resin, and the main agent is a hexamethylene diisocyanate prepolymer.
5. The high-efficiency microwave-absorbing composite coating for microwave deicing of wind turbine blades according to claim 3 is characterized in that: The contents of the components in the primer filled with carbon nanotubes are 2-6 wt.% of carbon nanotubes, 5-10 wt.% of diluent, and 84-93 wt.% of solvent-free polyurethane primer coating.
6. The high-efficiency microwave-absorbing composite coating for microwave deicing of wind turbine blades according to claim 4 is characterized in that: The contents of the components of the silicon carbide filled topcoat are 5-10wt.% of silicon carbide, 5-10wt.% of diluent, and 80-90wt.% of waterborne polyurethane topcoat coating.
7. The high-efficiency microwave-absorbing composite coating for microwave deicing of wind turbine blades according to claim 1 is characterized in that: The carbon nanotubes are multi-walled carbon nanotubes with an inner diameter of 3 to 5 nm, an outer diameter of 8 to 15 nm, and a length of 3 to 12 μm.
8. The high-efficiency microwave-absorbing composite coating for microwave deicing of wind turbine blades according to claim 1 is characterized in that: The particle size of the silicon carbide is 1000-1500 meshes.
9. The high-efficiency microwave-absorbing composite coating for microwave deicing of wind turbine blades according to claim 5 or 6, characterized in that: The primer thinner is ethyl acetate or butyl acetate, and the topcoat thinner is deionized water.
10. The high-efficiency microwave-absorbing composite coating for microwave deicing of wind turbine blades according to claim 1, characterized in that: The thickness of the primer filled with carbon nanotubes is 200-600 μm, and the thickness of the topcoat filled with silicon carbide is 50-200 μm.
Citation Information
Patent Citations
Coating method for wind generating blade, used base paint and preparation method for base paint
CN101695689A
Microwave-absorbing wind power blade coating as well as preparation method and application thereof
CN104087059A
Quick-drying roller coating type water-based wind turbine blade finish paint and preparation method thereof
CN116676032A
Cited By
Preparation method and application of super-hydrophobic SiO2 / rGO composite coating
CN120464230A